ANTI-INFLAMMATORY ACTIVITY OF HASS AVOCADO EXTRICTS IN SOFT DOSAGE FORM - Aleksandrova, Oleksandra; Podkopaieva, Vladyslava (SWorld-Ger Conference proceedings, 2025)
The work investigates the anti-inflammatory activity of an experimental soft dosage form containing thick ethanol-water extracts from avocado peel and seeds, as well as hexane extract of avocado pulp. In a model of induced allylisothiocyanate edema, it wa